Química e cinema: um estudo sobre as possibilidades de inserção do filme Perdido em Marte nas aulas de Química - Silveira, Patrícia (2020)
This work aimed to investigate the possibility of inserting the film The Martian (2015), looking for relationships with concepts of Chemistry that could be explored in the classroom, in basic education. The choice of this work is due to its popularity and, mainly due to the protagonist surviving on the planet Mars due to the innumerable knowledge related to Chemistry, Physics, Biology and engineering. In addition, it is understood that films, when inserted in teaching and learning situations, allow spaces for socialization, reflection, criticism, and the production of new meanings for scientific concepts. For this reason, some excerpts from the film were selected and presented to students in the first year of high school, in a public school in the state of Minas Gerais. During the classes, it was found that students were curious to understand the scenes and verify the veracity of what was presented, seeking to understand the related chemical concepts. In this way, it is considered that the film The Martian makes it possible to rescue previous concepts and mediate new knowledge, based on discussion and socialization in the classroom. Then, a new analysis of the film was carried out, seeking to understand how the scenes would enable i) to sensitize, ii) to question, iii) to illustrate, iv) to simulate and, v) to promote debates during Chemistry classes, aiming at the meaningful learning of students. concepts. At the end of the work, an educational product was elaborated. Suggestions for activities for Chemistry classes based in the The Martian film, produced from the experiences lived at school and the reflections enhanced by the readings carried out throughout the process. This didactic sequence, points to the possibility of using a cinematographic work, such as the film The Martian, in classroom. The suggestions contained therein, can support the work of the teacher, in order to support him in his pedagogical function. It is hoped that the selected scenes can support the professional, raising ideas, information, concepts and suggestions to improve the teaching and learning processes in Chemistry. In addition, the educational product gives the Chemistry teacher the opportunity to discuss the scientist's role as a social agent and its implications on ethical, environmental and cultural issues.